Basic measurements of radiation at station Lampedusa (2023-12 et seq) - Daniela Meloni; Damiano Massimiliano Sferlazzo (PANGAEA, 2024)
This is a compilation of all radiation datasets from Lampedusa station (https://www.lampedusa.enea.it/) that were published in the frame of BSRN. New data will be added regularly. The data are subject to the data release guidelines of BSRN (https://bsrn.awi.de/data/conditions-of-data-release/).